Impacts of the COVID-19 pandemic on international academic study exchange and research mobility programs - Dahdouh-Guebas, Farid; Vandebroek, Ina (Ethnobiology and Conservation, 2021)
In the wake of the COVID-19 pandemic, international exchange students and mobility researchers are probably the most neglected group within academia. We highlight their challenges within academia and society and we propose solutions towards academic flexibility, mobility preparedness and cultural immersion in host communities.